The surgical treatment of toxic megacolon in Hirschsprung disease - Khasanov, Rasul; Schaible, Thomas; Wessel, Lucas; Hagl, Cornelia Irene (Pediatric emergency care, 2016)
Objectives Enterocolitis remains the most significant cause of morbidity and mortality in Hirschsprung disease (HD). It could progress into toxic megacolon (TM)—acute dilatation of the colon as accompanying toxic complication of Hirschsprung enterocolitis. It is a devastating complication, especially in infants with so far undiagnosed HD. - Methods A retrospective analysis of medical records of 4 infants with TM was performed. The diagnosis TM was determined on the basis of clinical information (abdominal pain or tenderness, abdominal distension, diarrhea, bloody diarrhea, and constipation), plain x-rays of the abdomen (segmental or total colonic dilation), and the presence of such criteria (fever, high heart rate, increased white blood cell count, C reactive protein, anemia, dehydration, electrolyte disturbances, hypotension). Surgical management and outcome was evaluated by retrospective chart review. - Results The median duration of symptoms characteristic for TM was 3 days. Toxic megacolon was seen as the first manifestation of previously unknown HD in 3 patients; in 1 newborn, the contrast radiograph was suggestive of HD. In all patients, conservative treatment was failed. Three patients were treated with surgical decompression and ileostomy only. In all these cases, severe complications occurred, consequently 2 of them died. In 1 patient, a resection of the transverse dilated colon additionally was performed. This patient had no complications in postoperative period and survived. - Conclusions Because of the high mortality in patients with TM that were treated medically or with colonic decompression, a resection of massively distended part of the colon should be performed.